2014
DOI: 10.3109/14397595.2014.985356
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Castleman disease mimicking IgG4-related disease: A case report

Abstract: A 50-year-old woman was referred to our hospital for shoulder joint stiffness. She had a history of polyclonal hypergammaglobulinemia and an elevated C-reactive protein level. Her laboratory data revealed an elevated serum immunoglobulin G4 (IgG4) level, hypergammaglobulinemia, and rheumatoid factor positivity in the absence of anticyclic citrullinated peptide antibody. [18]-Fluorodeoxyglucose positron emission tomography showed significant [18]-fluorodeoxyglucose uptake in multiple lymph nodes (axillary, hila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Whether cardiovascular patients with IgG4-positive cell infiltration have a different clinical course [ 23 ] and an altered responsiveness to drug therapy as compared with those without IgG4-positive cell infiltration should be analyzed in future longitudinal studies. Third, IgG4-positive lymphoplasmacytic infiltration is not a feature exclusive to IgG4-RD; it may be observed in several immune and/or inflammatory disorders such as Castleman disease [ 24 ], Rosai-Dorfman disease [ 25 ], Wegener granulomatosis [ 26 ], and sialadenitis caused by sialolithiasis [ 27 ]. Lastly, we examined the presence or absence of IgG4-positive cell infiltration in one slide for each of the 103 samples; therefore, the true prevalence of IgG4-positive cell infiltration among these surgical samples might have been greater than what we have observed.…”
Section: Discussionmentioning
confidence: 99%
“…Whether cardiovascular patients with IgG4-positive cell infiltration have a different clinical course [ 23 ] and an altered responsiveness to drug therapy as compared with those without IgG4-positive cell infiltration should be analyzed in future longitudinal studies. Third, IgG4-positive lymphoplasmacytic infiltration is not a feature exclusive to IgG4-RD; it may be observed in several immune and/or inflammatory disorders such as Castleman disease [ 24 ], Rosai-Dorfman disease [ 25 ], Wegener granulomatosis [ 26 ], and sialadenitis caused by sialolithiasis [ 27 ]. Lastly, we examined the presence or absence of IgG4-positive cell infiltration in one slide for each of the 103 samples; therefore, the true prevalence of IgG4-positive cell infiltration among these surgical samples might have been greater than what we have observed.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic lymphadenitis and lymphoid hyperplasia associated with the disease are mostly detected in lymph node biopsies, so there are some deficiencies in confirming CD via needle biopsy. Based on the diagnostic criteria for CD, with the exception of the characteristic clinicopathological changes of patients, other related primary changes are often excluded in clinical diagnosis, thus, connective tissue disease, tumor disease, and infectious disease should be excluded in clinical diagnosis of CD, so as to improve the accuracy, sensitivity and specificity of clinical diagnosis [ 20 ]. The limitations in this study were that the potential value of IL-6 and CRP as diagnostic markers of CD children requires further validation within a large sample size, and by using comparison of histological and immunohistochemical analysis, including staining for CD3, CD5, CD10, CD20, CD23, CD79, and Ki-67 as previously reported [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two years after rituximab treatment, the patient's disease was stable with PSL (0.2 mg/kg). Izumi et al [22] reported a 50-year-old woman with characteristic feat u r e s o f M C D , i n c l u d i n g p o l y c l o n a l hypergammaglobulinemia, multiple enlarged lymph nodes, and pulmonary interstitial infiltration, with elevated serum IgG4 level and a 37.3% IgG4+/IgG+ plasma cell ratio in her biopsy specimen, while without organ involvement of IgG4-RD, corticosteroid treatment resolved the serological and imaging abnormalities. The 14 IgG4-CD patients in present study showed relatively favorable response to glucocorticoid and immunosuppressant therapy, one untreated IgG4-CD patient was stable, during a 33 (4-56)-month follow-up, and this was the same as those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%